Adhesion of Dictyostelium Amoebae to Surfaces: A Brief History of Attachments - Mijanović, Lucija; Weber, Igor (Frontiers in Cell and Developmental Biology, 2022)
Adhesion of Dictyostelium amoebae to extracellular material relies on mechanisms that resemble the analogous process in animal cells. Notably, the cellular anchorage loci in Amoebozoa and Metazoa are both arranged in the form of discrete spots and incorporate a similar repertoire of intracellular proteins assembled into multicomponent complexes located on the inner side of the plasma membrane. Surprisingly, however, Dictyostelium lacks integrins, the canonical transmembrane heterodimeric receptors that dominantly mediate adhesion of cells to the extracellular matrix in multicellular animals. In this review article, we summarize the current knowledge about the cell-substratum adhesion in Dictyostelium, present an inventory of the involved proteins, and draw parallels with the situation in animal cells. The emerging picture indicates that, while retaining the basic molecular architecture common to their animal relatives, the adhesion complexes in free-living amoeboid cells have evolved to enable less specific interactions with diverse materials encountered in their natural habitat in the deciduous forest soil. Dissection of molecular mechanisms that underlay short lifetime of the cell-substratum attachments and high turnover rate of the adhesion complexes in Dictyostelium should provide insight into a similarly modified adhesion phenotype that accompanies the mesenchymal-amoeboid transition in tumor metastasis.